2006
DOI: 10.1161/01.atv.0000245794.45804.ab
|View full text |Cite
|
Sign up to set email alerts
|

N ε -(Carboxymethyl)lysine Depositions in Intramyocardial Blood Vessels in Human and Rat Acute Myocardial Infarction

Abstract: Objective-Advanced glycation end products (AGEs), such as N -(carboxymethyl)lysine (CML), are implicated in vascular disease. We previously reported increased CML accumulation in small intramyocardial blood vessels in diabetes patients. Diabetes patients have an increased risk for acute myocardial infarction (AMI). Here, we examined a putative relationship between CML and AMI. Methods and Results-Heart tissue was stained for CML, myeloperoxidase, and E-selectin in AMI patients (nϭ26), myocarditis patients (nϭ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 30 publications
6
57
0
Order By: Relevance
“…In addition, AGE deposition can indirectly augment diastolic LV stiffness through enhanced collagen formation and reduced nitric oxide bioavailability. Indeed, enhanced collagen formation in the presence of AGEs was confirmed in our recent study [40], and low myocardial nitric oxide bioavailability was previously demonstrated in HFREF patients [4,5]. Postmyocarditis patients with HFREF frequently show signs of persistent myocardial microvascular inflammation [38].…”
Section: Level Of Ecm: Fibrosis and Advanced Glycation End (Age) Prodsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, AGE deposition can indirectly augment diastolic LV stiffness through enhanced collagen formation and reduced nitric oxide bioavailability. Indeed, enhanced collagen formation in the presence of AGEs was confirmed in our recent study [40], and low myocardial nitric oxide bioavailability was previously demonstrated in HFREF patients [4,5]. Postmyocarditis patients with HFREF frequently show signs of persistent myocardial microvascular inflammation [38].…”
Section: Level Of Ecm: Fibrosis and Advanced Glycation End (Age) Prodsupporting
confidence: 73%
“…Postmyocarditis patients with HFREF frequently show signs of persistent myocardial microvascular inflammation [38]. This inflammation may facilitate AGE deposition [4] and may explain the preferential AGE deposition in small intramyocardial vessels of diabetic patients with HFREF. The clinical importance of endothelial AGE deposition was recently confirmed in hypertensive patients who showed im- Pharmacological Reports, 2009, 61, 139-145 proved endothelial function with a cross-link breaker [43].…”
Section: Level Of Ecm: Fibrosis and Advanced Glycation End (Age) Prodmentioning
confidence: 99%
“…The cardiovascular complications in diabetes are postulated to be due to the high levels of AGEs in the circulation [40]. In addition, CML has been found on the inner walls of arteries in patients suffering from an acute myocardial infarction in the absence of diabetes [41]. Importantly, in the present study diabetics were excluded and other comorbidities were not frequent enough to investigate their contribution to the increased AGE levels in COPD.…”
Section: Discussionmentioning
confidence: 74%
“…Development of the anti-CML monoclonal antibody used and the immunohistochemical staining technique have previously been described. 27,28 An immunohistochemical AGE score per square millimeter is reported and was derived as follows: Each positively stained vessel was given an intensity grade (1ϭweak staining, 2ϭmoderate staining, 3ϭintense staining), and the sum of all positively stained vessels multiplied by their intensity grade was subsequently divided by the slide area to yield an AGE score per square millimeter.…”
Section: Immunohistochemistrymentioning
confidence: 99%